2016
DOI: 10.1124/dmd.116.071811
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 24 CYP2D6 Variants on the Metabolism of Nebivolol In Vitro

Abstract: CYP2D6 is an important cytochrome P450 (P450) enzyme that metabolizes approximately 25% of therapeutic drugs. Its genetic polymorphisms may significantly influence the pharmacokinetics and pharmacodynamics of clinically used drugs. Studying the effects of CYP2D6 on drug metabolism can help reduce adverse drug reactions and therapeutic failure to some extent. This study aimed to investigate the role of CYP2D6 in nebivolol metabolism by evaluating the effect of 24 CYP2D6 variants on the metabolism of nebivolol i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 15 publications
4
20
2
Order By: Relevance
“…Furthermore, the most meaningful difference between our study and previous reports19,2124 is that gefitinib exhibited a substrate inhibition trend of metabolic ability by CYP2D6 in vitro. Twenty-three tested CYP2D6 allelic variants showed this substrate inhibition trend toward gefitinib and their K si values varied from ~6 to 158 μM.…”
Section: Discussioncontrasting
confidence: 96%
See 3 more Smart Citations
“…Furthermore, the most meaningful difference between our study and previous reports19,2124 is that gefitinib exhibited a substrate inhibition trend of metabolic ability by CYP2D6 in vitro. Twenty-three tested CYP2D6 allelic variants showed this substrate inhibition trend toward gefitinib and their K si values varied from ~6 to 158 μM.…”
Section: Discussioncontrasting
confidence: 96%
“…In addition, different from the previous studies,19,2124 the metabolic ability toward gefitinib in vitro exhibited substrate inhibition trend, the inhibition constant of 25 tested CYP2D6 variants varied from nearly 5.9 to 158.1 μM.…”
Section: Resultscontrasting
confidence: 84%
See 2 more Smart Citations
“…It has been proven that nebivolol bioavailability was greater for the CYP2D6 poor metabolizers in comparison with CYP2D6 extensive metabolizers, suggesting the potential need for individualized treatment strategies . Most studies have concentrated primarily on the influence of the CYP2D6 genotype/phenotype on the clinical response and metabolism of nebivolol, which is a metabolic pathway that is under polymorphic regulation . However, our previous study showed that CYP2C19 and CYP3A4 can contribute, to some extent, to this pathway for the metabolism of nebivolol 4‐hydroxylation .…”
Section: Introductionmentioning
confidence: 99%